(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The quality of electrical energy has become a strategic issue for all economic actors. Its efficiency is reduced due to multiple disturbances and harmonic injections caused by the different connected loads. The electric vehicle (EV) takes an important place among these loads that take their energy from the grid through charging stations. In this paper, a solution to improve the power factor and reduce the harmonic injection is proposed by introducing a power factor correction (PFC) circuit in the charging stations. It is realized by a single-ended primary-inductor converter (SEPIC) that allows isolation between the load and the electrical network. In addition, it offers hardware minimization since it operates simultaneously in boost and buck without polarity reversal. A control technique based on the use of the sliding mode control (SMC) technique is proposed for harmonic reduction and power factor correction. SMC is used to maintain the output voltage of the SEPIC converter at its desired value, improve the power factor (PF) and reduce the total harmonic distortion (THD). A software-in-the-loop (SIL) simulation using a real-time simulation platform (RT LAB) is performed to confirm the system performance.